Nontuberculous mycobacteria infection and pulmonary disease in bronchiectasis. Issue 4 (12th December 2022) - Suska, Kseniia; Amati, Francesco; Sotgiu, Giovanni; Gramegna, Andrea; Mantero, Marco; Ori, Margherita; Ferrarese, Maurizio; Codecasa, Luigi Ruffo; Stainer, Anna; Blasi, Francesco; Aliberti, Stefano
Background: Although interest in nontuberculous mycobacteria (NTM) infection has increased in the last decades, published data vary according to different geographical areas, diagnostic facilities and quality of study design. This study aims at assessing both prevalence and incidence of NTM infection and NTM pulmonary disease (NTM-PD) among adults with bronchiectasis, to describe patients' characteristics, therapeutic options and clinical outcomes. Methods: Bronchiectasis adults who had been tested for NTM were enrolled at the Bronchiectasis Program of the Policlinico Hospital in Milan, Italy, from 2016 to 2018. Results: Among the 373 patients enrolled, 26.1% had at least one respiratory sample positive for NTM and 12.6% reached a diagnosis of NTM-PD. Incidence rates for NTM infection and NTM-PD were 13 (95% CI 10–16) and 4 (95% CI 2–6) per 100 person-years, respectively. The most prevalent NTM species causing NTM-PD were M. intracellulare (38.3%), M. avium (34.0%), M. abscessus (8.5%) and M. kansasii (8.5%). Once treatment for NTM-PD was initiated, a favourable outcome was documented in 52.2% of the patients, while a negative outcome was recorded in 32.6%, including recurrence (17.4%), treatment failure (10.9%), re-infection (2.2%) and relapse (2.2%). Treatment halted was experienced in 11 (23.9%) patients. Conclusions: NTM infection is frequent in bronchiectasis patients and the presence of NTM-PD is relevant. The low success rate of NTM-PD treatment in bronchiectasis patients requires a call to action to identify new treatment modalities and new drugs to improve patients' outcomes. The low success rate of NTM pulmonary disease treatment in bronchiectasis patients necessitates a call to action to find novel treatment modalities and new drugs to improve outcomes https://bit.ly/3aNcBVd